PERFORMANCE OF CONCRETE MADE WITH CRUSHED CLAY BRICKS AS COARSE AGGREGATE - QOJA, GHANIM HU SSEIN; DINKHA, YOUKHANNA ZAYIA (Journal of Duhok University, 2017)
Because of economic considerations and thermal insulation requirements, it seems necessary therefor to produce lightweight concrete obtained by crushing an enormous tons of building demolition wastes have been produced. In this study, it is gintended to investigate smashed and the possibility of using crushed clay bricks to replace the coarse aggregate (gravel) in concrete mies. Four nominal normal concrete mixes and four more mixes of crushed clay brick aggregate were prepared and tested. The crushed clay brick aggregates were produced by crushing the brick units (locally available and manufactured in Iran) manually and collected into described size (20 mm). From the analysis of the results, it was found that the unit weight of the crushed brick concrete ranged from (1685-1760) kg/m3 and its compressive strength was about 61% of that of the natural aggregate concrete while the flexural strength was 70% of natural aggregate concrete. Also, the relation between compressive and flexural strength for the lightweight concrete produced is similar to that of normal concrete. Moreover, the results indicated the suitability of the crushed clay brick aggregate concrete to be used in buildings.